Axillary evaluation in ductal cancer in situ of the breast: challenging the diagnostic accuracy of clinical practice guidelines. Issue 9 (5th June 2021) - Karakatsanis, Andreas; Charalampoudis, Petros; Pistioli, Lida; Di Micco, Rosa; Foukakis, Theodoros; Valachis, Antonios; ,
Abstract: Background: Staging of the axilla is not routine in ductal cancer in situ (DCIS) although invasive cancer is observed in 20–25 per cent of patients at final pathology. Upfront sentinel lymph node dissection (SLND) is advocated in clinical practice guidelines in certain situations. These include expected challenges in subsequent SLN detection and when the risk for invasion is high. Clinical practice guidelines are, however, inconsistent and lead to considerable practice variability. Methods: Clinical practice guidelines for upfront SLND in DCIS were identified and applied to patients included in the prospective SentiNot study. These patients were evaluated by six independent, blinded raters. Agreement statistics were performed to assess agreement and concordance. Receiver operating characteristic curves were constructed, to assess guideline accuracy in identifying patients with underlying invasion. Results: Eight guidelines with relevant recommendations were identified. Interobserver agreement varied greatly (kappa: 0.23–0.9) and the interpretation as to whether SLND should be performed ranged from 40–90 per cent and with varying concordance (32–88 per cent). The diagnostic accuracy was low with area under the curve ranging from 0.45 to 0.55. Fifty to 90 per cent of patients with pure DCIS would undergo unnecessary SLNB, whereas 10–50 per cent of patients with invasion were not identified as 'high risk'. Agreement across guidelines was low (kappa = 0.24), meaning that different patients had a similar risk of being treated inaccurately. Conclusion: Available guidelines are inaccurate in identifying patients with DCIS who would benefit from upfront SLNB. Guideline refinement with detailed preoperative work-up and novel techniques for SLND identification could address this challenge and avoid overtreatment. Lay summary: The decision whether to operate on the axilla in women with a diagnosis of ductal cancer in situ (DCIS) is based on the risk of an undiagnosed underlying invasive cancer and on the concern that resection of the breast will not allow for accurate axillary mapping afterwards. Guidelines stem from older knowledge and are heterogeneous. In this study, different breast cancer guidelines were tested in a patient cohort from the SentiNot prospective trial for uniformity of interpretation and diagnostic accuracy. Results show that guidelines did not allow for easy and uniform interpretation and had the predictive ability of the toss of a coin. This suggests that guidelines regarding the need of axillary evaluation in patients operated for DCIS need to be revised and that techniques that will address the conundrum should be developed. Abstract : Guidelines on axillary surgery for DCIS are unclear. Different guidelines were validated using a dataset from the prospective SentiNot study.